Nursing Entrepreneurship Development: Literature Review - Asih Purwandari Wahyoe Puspita; Dinda Castury; Tirta Adikusuma Suparto; Yanti Hermayanti; Dian Rahayuningsih (Universitas Pendidikan Indonesia, 2021)
Background : Entrepreneurship in nursing has enormous and promising opportunities for a nurse. It includes palliative care / home care, nursing counseling, caregiver training, physiotherapy services and others. However, the development of entrepreneurship in nursing still faces several obstacles.Purpose The aim of this study was to explore the development of entrepreneurship in nursing.Method The method used in this study was literature review. Several data bases including Google schoolar, Garuda, National Library, DOAJ, PubMed, Sciencedirect, and Proquest were used. Keywords were chosenin accordance with MESH (Medical Subject Heading), including “kewirausahaan keperawatan”, “hambatan kewirausahaan keperawatan”,